A Comparison of a Single-Stimulation Lateral Infraclavicular Plexus Block With a Triple-stimulation Axillary Block. Issue 2 (1st March 2003) - Deleuze, Arnaud; Gentili, Marc E.; Marret, Emmanuel; Lamonerie, Laurent; Bonnet, Francis
Abstract : Background and Objectives: A single-stimulation infraclavicular brachial plexus block (ICB) is safe and easy to perform, although underused. This technique was compared with a triple-stimulation axillary block (AxB). Methods: One hundred patients scheduled for hand and forearm surgery were randomly allocated to 2 groups. ICB was performed with the needle inserted above the coracoid process in the upper lateral angle of the infraclavicular fossa and directed vertically until nerve stimulation elicited a distal motor response (median, radial, or ulnar). A single 40-mL bolus of ropivacaine 0.75% was injected. In the AxB group, 3 stimulations were performed to identify median or ulnar, radial, and musculocutaneous nerves, followed by an infiltration near the medial brachial and antebrachial cutaneous nerves. The same 40 mL ofropivacaine 0.75% was injected. Sensory and motor blocks were assessed at 5-minute intervals over 30 minutes. Results: The time to block performance was shorter in the ICB than in the AxB group (2.5 ± 1.9 minutes v 6.0 ± 2.8 minutes, P < .001). The success rate (complete block in median, radial, ulnar, musculocutaneous, and medial antebrachial cutaneous nerves) was comparable in the 2 groups (90% v 88% in groups ICB and AxB, respectively). Block extension was comparable, except for a higher rate of block completion in the axillary nerve distribution in group ICB and in the medial brachial cutaneous nerve in group AxB. The onset of each nerve block was comparable except for a faster onset for the musculocutaneous nerve in group AxB (8 ± 3 v 10 ± 5 minutes). Conclusion: A single shot ICB is equally effective as a triple-nerve stimulation AxB. Reg Anesth Pain Med 2003;28:89-94.